Life after tenure: Professional development strategies for mid‐career faculty. Issue 1 (27th December 2016) - Byström, Katriina; Given, Lisa M.; Lopatovska, Irene; O'Brien, Heather; Rorissa, Abebe
ABSTRACT: Many publications, institutional policies, and resources focus on the professional development of doctoral students and junior faculty while professional development needs and resources available to mid‐career faculty receive limited attention. The proposed panel aims to facilitate a discussion on issues faced by mid‐career faculty in the information disciplines. Professional development resources and strategies currently available to mid‐career faculty and administration will also be discussed. The panelists will include mid‐career and senior faculty from various institutions and information disciplines who will bring their multi‐disciplinary and international perspectives to the panel. The panel will be of interest to faculty and academic administrators at all‐levels of their careers.